Quantitation of the ROS production in plasma and radiation treatments of biotargets - Wan-Ook Ji (Nature Portfolio, 2019)
Abstract Medical treatment utilizing non-thermal plasma is based on the production of reactive oxygen species (ROS) and their interactions with biomatters. On the basis of empirical data from practices, plasma treatment has been planned with regard to the setup of a plasma generator’s parameters, including gas combination, gas-flow rate, and applied voltage. In this study, we quantitated plasma treatment in terms of the plasma dose on the target matter, which can be contrasted with the radiation dose to targets under radiation exposure. We measured the OH radical production in cell culture medium and intracellular ROS production from plasma treatment in comparison with those from X-ray exposure. The clonogenic cell deaths from plasma and X-ray exposures were also compared. In plasma treatment, the clonogenic cell death was better predicted by intracellular ROS production rather than by medium OH production.